Macroeconomic Impact on Population Density in Indonesia - Poddala, Anggi Somba (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to determine and analyze population density by looking at the influence of poverty, income, education, health and urbanization in Indonesia. This research uses panel data regression with the variables poverty, income, education, health, urbanization and population density with data analysis using SPSS 22 software. The research period is 2020-2022. The results of this study show that poverty, education and health are significant to urbanization. Meanwhile, income has no effect on urbanization. Poverty, income and health are directly significant to population density. Meanwhile, education and urbanization have no direct influence on population density. The indirect relationship between poverty, income, education and health has no effect on population density through urbanization